Lasuna rasayana in management of parkinsonism-a case report - R., Arathi; Giri, P. V. (International Journal of Research in Medical Sciences, 2024)
Parkinsonism is a disease with insidious onset and slow progression. It is one of the most common extrapyramidal disorders seen in clinical practice. Parkinsonism can be correlated with Kampavata in Ayurveda based on similar symptomatology. This case presents an intriguing scenario of Parkinsonism, with the patient having undergone allopathic medication for the last two years. Additionally, Ayurvedic treatments and Rasayana therapy have been introduced as complementary measures. The patient underwent Avaranagna and Vatavyadi chikitsa, incorporating practices such as Agni deepanam, Amapachanam, Snehana svedanam, Shodanam, and Rasayana chikitsa for a holistic therapeutic approach. Patients assessment was conducted using modified Hoehn and Yahr scale, Schwab and England ADL scale, Parkinson’s disease composite scale and PDQ 39 scale on the 0th day and 42th day. Quality of life scale PDQ-39 SI score was improved from 53.25 pre-treatment to 35.79 post treatment. Following 42 days of treatment incorporated with ayurvedic treatment procedures, coupled with Rasayana therapy, demonstrated a notable amelioration of symptoms, a reduction in disability, and an enhancement in the overall quality of life.